Tempeh with Iron Fortification to Overcome Iron Deficiency Anemia - Sudargo, Toto; Nisa, Fatma Zuhrotun; Helmiyati, Siti; Kusuma, Rio Jati; Arjuna, Tonny; Septiana, R. Dianandha (Pakistan Journal of Nutrition, 2013)
Prevalence of iron deficiency anemia in Indonesia is still high. Iron fortification in food may contribute to addressing iron deficiency anemia. This study was conducted to determine the effect of NaFeEDTA fortification on iron levels in tempeh and some organoleptic properties of fortified tempeh (TemFe), as well as to determine the effect of TemFe in hemoglobin levels and the bioavailability of iron on Wistar rats anemia. This study is divided into two phases, so there are two research design. The first phase is purely experimental with completely randomized design. The second phase is quasi experimental with pre and post control group design. Fortification of tempeh with NaFeEDTA significantly increased the iron levels in tempeh (p<0.05). The organoleptic test showed that there is no significantly difference either tempeh nor TemFe (p>0.05). There are significantly differences in hemoglobin levels in tempeh and TemFe administration at a dose of 24 ppm compared with FeSO4 with same dose (p<0.05). The relative bioavailability (RBV) value for TemFe and tempeh was 100.10 and 33.65%, respectively. The fortification of NaFeEDTA in tempeh can increase iron levels and did not alter the organoleptic properties. There is a significant increase of hemoglobin levels in anemic groups of Wistar rats that received TemFe with dose of 24 ppm. The bioavailability due to iron fortification in TemFe is higher than that of the tempeh and FeSO4 as a gold standard.